Pentoxifylline and its applications in dermatology - Hassan, Iffat (Indian Dermatol Online J, 2014)
Pentoxifylline is a methyl-xanthine derivative with many anti inflammatory effects. Pentoxifylline has been found to be effective for many dermatological as well as non-dermatological conditions. It has been used both as primary drug as well as adjuvant and is a safe and relatively cost-effective alternative drug. In this article, we review the literature and highlight various important aspects of pentoxifylline.